A mística da profissionalização docente - Eneida Shiroma Oto; Olinda Evangelista (Universidade do Minho, 2003)
The educational reforms developed by the government of Fernando Henrique Cardoso (1995-2002) to attack the supposed inefficiency and bad quality of state schools, have had the paradoxical effect of disqualifying many teachers in elementary schools. In this context, the State selected the professionalization of teachers as the pivot of the changes that it sought. It aimed to produce new meanings for the idea of teacher professionalism. The intention of this article is to discuss the use of the notion of professionalization and the centrality attributed to the teacher, associating them with the solution of problems related not only to education, but also to the economic and political spheres. We suggest that the term professionalization is intentionally reiterated in teacher training policy documents because of its positive connotations in common parlance and its ability to produce certain effects as a result of this. The concept is therefore used as a strategy to build a consensus between educators and reformers about the hegemonic project of education and society.